Colour image in 2D and 3D microscopy for the automation of pollen rate measurement - Bonton, Pierre (Image analysis and stereology, 2002)
Pollen monitoring is of great importance for the prevention of allergy. As this activity is still largely carried out by humans, there is an increasing interest in the automation of pollen monitoring. The goal is to reduce monitoring time in order to plan more efficient treatments. In this context, an original device based on computer vision is developed. The goal of such a system is to provide accurate measurement of pollen concentration. This information can be used as well by palynologists, clinicians or by a forecast system to predict pollen dispersion. The system is composed of two modules: pollen grain extraction and pollen grain recognition. In the first module, thepollen grains are observed in light microscopy and are extracted automatically from a microscopic slide dyed with fuchsin and digitised in 3D. The colour segmentation techniques implemented on a hardware architecture are presented. In the second module, the pollen grains are analysed for recognition. To accomplish recognition, it is necessary to work on 3D images and to use deep palynological knowledge. This knowledge describes the pollen types according to their main visible characteristerics and to those which areimportant for recognition. Some pollen structures are identified, like the pore with annulus in Poaceae, the reticulum in Olea and similar pollen types or the cytoplasm in Cupressaceae. Preliminary results show correct recognitionof some pollen types, like Urticaceae or Poaceae, and some groups of pollen types, like reticulate group.
Keywords: Cvetni prah; Pollen; Particle Size; Delec, velikost; Pattern Recognition; Mikroskopija; Slika, obdelava z računalnikom; Microscopy; Image Processing, Computer-Assisted; Vzorec, razpoznavanje; slikovna diagnostika; analiza slik; pelodne analize